Morphogenetical Karst Types of the Transylvanian Mountains (Mt. Apuseni - Móga, János (Acta Carsologica, 2016)
V vseh Karpatih so kraški pojavi najbolje razviti v Transilvanskem gorovju (Apusenih), med Transilvansko kotlino in Veliko madžarsko ravnino. Ti pojavi so skladni z različno sestavo in različno kamninsko zgradbo ozemlja ter z različno naravo denudacijskih procesov. Avtor podaja pregled in morfogenetsko sistemizacijo tega najbolj zanimivega kraškega ozemlja. The most well developed karstic forms in the whole of the Carpathians emerged in the Transylvanian Mountains (Mt. Apuseni) situated between the Transylvanian basin and the Great Hungarian Plain. This phenomena correlates with the diversity of structure and rock formation, and to the multifold nature of denudation processes. My intention is to present a survey and morphogenetic systematization of the most interesting karstic regions.